Humour in Indonesia EFL classroom: A qualitative study - Purwanti, Eko; Fitria Ulinnuha; Gendroyono, Gendroyono (Teaching English as a Foreign Language Journal, 2024)
English as a Foreign Language (EFL) lessons can be challenging, particularly for students with limited English proficiency. In Indonesia, creating a relaxed classroom environment is essential for effective language acquisition. Consequently, teachers often incorporate humour as a pedagogical strategy. Despite its potential benefits, the use of humour in EFL classrooms remains underexplored. This study aims to identify the types of humour employed by teachers and examine students' responses to these humorous interventions. Utilizing a qualitative approach with a descriptive research design, this study was conducted in the English Language Education Department of a private university in Yogyakarta. Data were collected through three classroom observations and interviews with six third-year students. The findings reveal six types of humour used in the classroom: 1) teasing, 2) self-disparaging humour, 3) lesson-related humour, 4) sarcasm, 5) hilarious comments, and 6) gestures. Additionally, the study identifies seven student responses to teachers' humour: 1) fostering enjoyable learning activities, 2) stimulating student interest, 3) reducing classroom anxiety, 4) assisting comprehension of materials, 5) motivating class participation, 6) alleviating tension and boredom, and 7) enhancing student engagement. Based on these findings, it is recommended that humour be integrated into EFL classrooms due to its numerous benefits for both students and teachers, as well as its positive impact on the learning environment.